Management strategies of social welfare institutions in optimizing service delivery for vulnerable groups amid contemporary social dynamics - Stella Theodora Kewo; Lady Galatia Lapian (Indonesian Institute For Counseling, Education and Therapy, 2026)
Contemporary social dynamics have intensified and diversified vulnerability, challenging social welfare institutions to move beyond static and linear service delivery models. Existing literature highlights that service effectiveness is strongly shaped by governance structures, organizational capacity, and performance management systems, including the use of key performance indicators (KPIs) and monitoring mechanisms. However, many institutional responses remain reactive and fragmented, resulting in service gaps and misalignment between policy design and implementation. This study adopts a library-based approach using content analysis to examine how management strategies can optimize service delivery for vulnerable groups. The findings suggest that adaptive governance, data-driven evaluation, cross-sector collaboration, and continuous performance monitoring are critical components of effective strategy. Ultimately, optimizing service delivery depends on the integration of strategic planning and operational responsiveness to evolving patterns of vulnerability.